Social Factors and Social Media Usage Activities on Customer Path 5A Continuity Due to E-Marketing Communication - Agustina Multi Purnomo (International Journal of Social Science and Business, 2023)
The customer path 5A approach proposed the customer's personalization and communication on social media marketing. The previous studies suggested the influence of customer's social factors were age, gender, income, and occupation on customer path 5A due to X's e-marketing communication. This study added social media usage activity. However, the previous study did not analyze the customer's role in path 5A phase continuity. This study examined the influence of social factors and social media usage activity on the consumer path 5A continuity due to restaurant X's e-marketing communication. The research method was quantitative, with a survey of 400 samples. The samples were taken from Instagram followers and average monthly visitors of restaurant X in 2021, or 11,400 people. The one-way ANOVA tests found that customers' social factor was significantly different in influencing customer path 5A was the occupation. The social media usage activity was another factor influencing customer path 5A was the internet spending category. The two customer factors influenced the partial customer path 5A category and did not denote the customer path 5A phase continuity as the previous study suggested. Further research is needed to explain the reason for the discontinuity between each customer Path 5A's phase.